Production of Plasmodium vivax enolase in Escherichia coli and its protective properties. Issue 11 (1st November 2016) - Zhang, Chao; Gu, Yaping; Tang, Jianxia; Lu, Feng; Cao, Yuanyuan; Zhou, Huayun; Zhu, Guoding; Cao, Jun; Gao, Qi
ABSTRACT: Plasmodium vivax predominates in South-East Asia and the American continent, causes significant morbidity and inflicts a huge socioeconomic burden. Sequencing completion of the Plasmodium vivax genome and transcriptome provides the chance to identify antigens. Enolase is the eighth enzyme in the glycolytic pathway, which, apart from its glycolytic function, also possess antigenic properties and is present on the cell wall of many invasive organisms, such as Candida albicans. In order to assess whether enolase of Plasmodium vivax is also antigenic, in this study, we first reported the expression and purification of recombinant Plasmodium vivax enolase (r-Pven) in Escherichia coli, using prokaryotic expression vector. The r-Pven was expressed in soluble form in E. coli, and the expression was verified by SDS-PAGE and western blotting analysis. The r-Pven was purified to 90% purity by nickel–nitrilotriacetic acid (Ni 2+ –NTA) resin chromatography. For reactivity with r-Pven, compared with the average values of the reactivity of control serum samples, the average values of the reactivity of 99 individual serums from vivax malaria patients appeared higher, and there was significant difference between them (p=0.0117<0.05). Mice anti-r-Pven antibodies inhibited the growth of in vitro cultures of P. falciparum. Mice immunized with r-Pven showed protection against a challenge with the mouse malarial parasite Plasmodium berghei. The antibodies raised against r-Pven were specific for Plasmodium and did not react to the host tissues. These observations established Plasmodium vivax enolase to be a potential protective antigen.